2020
DOI: 10.1177/1073274820977135
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Reduction of Neutrophil-to-Lymphocyte Ratio Is Associated With Better Survival in Pancreatic Adenocarcinoma: A Meta-Analysis

Abstract: Objectives: Numerous studies have suggested that an increase in neutrophil-to-lymphocyte ratio (NLR) before treatment is associated with worse survival in pancreatic adenocarcinoma (PAC). The aim of this study was to investigate the prognostic value of treatment-induced NLR change among PAC patients so as to better identify the characteristics of those who can benefit more from treatment. Methods: This meta-analysis was undertaken using the PRISMA statement. Previously published studies between the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“… 17 A meta‐analysis reported that chemotherapy‐induced reduction of NLR is associated with better survival in pancreatic cancer. 18 In other words, the immune cell status just before immunotherapy is important for the efficacy of ICIs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 17 A meta‐analysis reported that chemotherapy‐induced reduction of NLR is associated with better survival in pancreatic cancer. 18 In other words, the immune cell status just before immunotherapy is important for the efficacy of ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that prepembrolizumab NLR predicts the efficacy of second‐line pembrolizumab in urothelial cancer regardless of prechemotherapy NLR 17 . A meta‐analysis reported that chemotherapy‐induced reduction of NLR is associated with better survival in pancreatic cancer 18 . In other words, the immune cell status just before immunotherapy is important for the efficacy of ICIs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The NLR has therefore been considered a novel prognostic indicator (30,31). It is also reportedly associated with the responses of several cancers to chemotherapy (32)(33)(34)(35), indicating it potentially has value as a biomarker for predicting sensitivity to chemotherapy. Blood cell counts are routinely checked at the beginning of diagnosis or treatment, making the NLR a convenient, cost-effective, and reproducible marker in clinical practice.…”
Section: Discussionmentioning
confidence: 99%